a process of idolatries extirpation in the Parish of aija’s santiago, Huaylas’s doctrine, 1672 - León Fernandez, Dino (2013)
This article comprises the proceedings in the town of Santiago province Aija in the path of Huaylas. It is a denunciation of idolatrand other excesses that the cacique Don Diego de Yaruparia committed in his village in 1672, and documentation consists of 38 folios votes. The person in charge of the investigation was the visitor Ignacio Castelbi, by special request of Archbishop Pedro de Villagomez. The mission was entrusted to the removal and punishment of idolatry and superstition existing among the Indians of the province of Huaylas.